Aktionsprofil und Stoffwechsel des Amateurboxens im drei mal zwei Minuten Format - Beneke, R.; Davis, P.; Leithäuser, R. M. (Leipziger Sportwissenschaftliche Beiträge, 2013)
An activity profile of competitive three times two minutes novice level amateur boxing was created based on video footage in thirty-two male boxers which served as template to simulate amateur boxing for metabolic analyses. The activity profile identified that landing punches requires the ability to maintain a high frequency of attacking movements in particular the straight punch lead hand together with punching combinations. Defensive movements must initiate a counter-attack. The simulation of competitive three times two minutes novice level amateur boxing combined with respiratory gases and lactate measurements demonstrated that with 73 % aerobic, 23 % anaerob-PCr-derived and 5 % anaerob-glycolytic energy three times two minutes novice level amateur boxing relies dominantly on aerobic energy.